Aerosol Sampling in a Hospital Emergency Room Setting: A Complementary Surveillance Method for the Detection of Respiratory Viruses - Choi, Jessica Y.; Zemke, Juliana; Philo, Sarah E.; Bailey, Emily S.; Yondon, Myagmarsukh; Gray, Gregory C. (Frontiers in Public Health, 2018)
This study aimed to evaluate environmental air sampling as an alternative form of active surveillance for respiratory pathogens in clinical settings. Samples were collected from three locations in the Emergency Department at Duke University Hospital Systems from October 2017 to March 2018. Of the 44 samples collected, 12 were positive for known respiratory pathogens including influenza A, influenza D, and adenovirus. Results suggest bioaerosol sampling may serve as a complement to active surveillance in clinical settings. Additionally, since respiratory viruses were detected in aerosol samples, our results suggest that hospital infection control measures, including the use of N95 respirators, could be used to limit the spread of infectious viruses in the air.